BACTERICIDAL PROPERTIES OF THE “DOROSEPT SUPER”AGENT FOR MYCOBACTERIA - Paliy, A. P.; Zavgorodniy, A.I.; Bondarchuk, A. O. (Scientific Progress & Innovations, 2019)
At present, disinfectants, which are used in livestock buildings, are different as to concentration of active substances, composition, application and a number of other properties. Most of them are imported commercial products. The relevance of the research is to replace them on the domestic market with more effective, safe and cost-efficient preparations. Such products must be highly effective and have a wide range of bactericidal, virucidal, fungicidal and sporocidal action. The improvement of livestock’s health after infectious diseases, especially tuberculosis, which causes significant economic losses to this sector and threatens human health, is one of the important tasks of veterinary medicine specialists. The spreading of tuberculosis causal agents and atypical mycobacteria in the environment demands from specialists to use highly effective antimicrobial preparations to prevent further persistence of these microorganisms, as well as infecting farm animals. Ukrainian and foreign manufacturers recommend a great number of disinfectants, which are rather effective in the prevention and elimination of most infectious diseases. However, it should be noted that not all disinfectants are effective enough for tuberculosis infection. This paper presents the study results of the bactericidal properties of the “DOROSEPT SUPER” disinfectant as related to Mycobacterium fortuitum, as well as Mycobacterium bovis on test objects. The suspension method has shown that Mycobacteria fortuitum die after applying aqueous disinfectant solution at a concentration of 1.0 % and exposure of 1 hour. After the treatment of wooden, batiste, metal, tile and glass test objects, which were contaminated with M. bovis, the viability of the latter ceased after 24 hours under the influence of 3% preparation concentration. Moreover, while applying an aqueous solution to the same test objects in an operating mode of 1.0 % − 24 hours, mycobacteria died in all cases, except those that were applied to wooden surface. The results of biological study of the “DOROSEPT SUPER” disinfectant were also presented in the article.